Do Managerial and institutional Ownership, Company Growth and Size effect on Debt Policy? - Rivani, Dian; Ghazali, Muhammad; Oktavia, Dinda (SAN Scientific, 2024)
This research aims to examine the influence of managerial ownership, institutional ownership, company growth, and company size on debt policy. This research uses descriptive quantitative type. This research uses a population of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sampling technique in this research was purposive sampling, and a sample of 7 companies was obtained. This research uses secondary data, namely annual financial reports obtained from the official website of the Indonesian Stock Exchange (IDX). The analytical method used is multiple regression analysis. The research results show that managerial ownership, institutional ownership, company growth, and company size do not affect debt policy. Managerial implications. Firstly, discuss implications related to managerial ownership. Second, discuss implications related to institutional ownership. Thirdly, discuss implications related to company growth. Lastly, discuss implications related to company size. Understanding these implications can aid managers in formulating effective debt policies to optimize firm performance and mitigate financial risks. Further research avenues are also suggested to deepen the understanding of these dynamics. They need to understand the risks and potential benefits of using debt, as well as consider external factors such as market conditions and regulations.